Bordetella pertussis in children hospitalized with a respiratory infection: clinical characteristics and pathogen detection in household contacts - del Valle-Mendoza, Juana (2018)
Objective: Describe the prevalence of Bordetella pertussis via PCR in children under 5 years old hospitalized as probable cases of pertussis and report the most common clinical features among them. Results: A positive PCR result for B. pertussis was observed in 20.5% of our samples (18/88), one-third of them were from infants between 2 and 3 months old. The most common symptoms were paroxysms of coughing (88.9%), difficulty breathing (72.2%), cyanosis (77.8%) and fever (50%). The mother was the most common symptomatic carrier (27.8%), followed by uncles/aunts (22.2%) among children with pertussis.